Kajian Kemampuan Adaptasi Industri Kecil Dan Menengah Terhadap Bencana Banjir Dan Rob: Studi Kasus Sentra Industri Bandeng Presto Kelurahan Tambakrejo Kota Semarang - Syarif Hidayatullah; Mohammad Muktiali (Teknik PWK (Perencanaan Wilayah Kota), 2021)
Tambakrejo Village is one of the villages in Semarang City with high flood and tidal potential, this is because the location of the village is adjacent to the Banjir Kanal Timur River and the Java Sea. The Tambakrejo Village by the Semarang City Government was used as one of the thematic villages for the development of regional potential, with the potential of the Tambakrejo Village being a small and medium industry, namely the Bandeng Presto center. This research was conducted to examine the adaptability capabilities of existing small and medium industries to the disasters that occurred. This research uses descriptive quantitative method with data obtained using a questionnaire from 10 business units and 47 workers. The results showed that the level of industrial adaptation is still relatively low from a total of 10 business units only 4 business units that do adaptation while from the labor side, only 12 out of a total of 47 workers, both from building adaptation, adaptation to business continuity and adaptation at the community level which makes the level of industrial resilience low.